1997
DOI: 10.1002/(sici)1096-9861(19970922)386:2<317::aid-cne11>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Use of calcium-binding proteins to map inputs in vestibular nuclei of the gerbil

Abstract: We wished to determine whether calbindin and/or calretinin are appropriate markers for vestibular afferents, a population of neurons in the vestibular nuclear complex, or cerebellar Purkinje inputs. To accomplish this goal, immunocytochemical staining was observed in gerbils after lesions of the vestibular nerve central to the ganglion, the cerebellum, or both. Eleven to fourteen days after recovery, the brain was processed for immunocytochemical identification of calretinin and calbindin. After lesion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…For calbindin and parvalbumin, but not calretinin, a second major source is Purkinje cells of the cerebellum (Celio 1990). Work in the rodent suggests that the cerebellum and the eighth nerve are in fact the only sources of calbindin-immunoreactive fibers in the VNC (Kevetter and Leonard 1997;Bäurle et al 1998). The possible sources of parvalbuminimmunoreactive fibers are more numerous, as several brainstem structures with parvalbuminimmunoreactive cells, including the interstitial nucleus of Cajal (Kokkoroyannis et al 1996;Horn et al 1999), the rostral interstitial nucleus of the MLF (Horn and Büttner-Ennever 1998) and inhibitory and excitatory burst neurons of the reticular formation (Horn et al 1995) may contribute the parvalbumin-immunoreactive fibers that are seen in the MLF and VNC.…”
Section: Sources Of Calretinin Calbindin and Parvalbumin Fibersmentioning
confidence: 99%
See 2 more Smart Citations
“…For calbindin and parvalbumin, but not calretinin, a second major source is Purkinje cells of the cerebellum (Celio 1990). Work in the rodent suggests that the cerebellum and the eighth nerve are in fact the only sources of calbindin-immunoreactive fibers in the VNC (Kevetter and Leonard 1997;Bäurle et al 1998). The possible sources of parvalbuminimmunoreactive fibers are more numerous, as several brainstem structures with parvalbuminimmunoreactive cells, including the interstitial nucleus of Cajal (Kokkoroyannis et al 1996;Horn et al 1999), the rostral interstitial nucleus of the MLF (Horn and Büttner-Ennever 1998) and inhibitory and excitatory burst neurons of the reticular formation (Horn et al 1995) may contribute the parvalbumin-immunoreactive fibers that are seen in the MLF and VNC.…”
Section: Sources Of Calretinin Calbindin and Parvalbumin Fibersmentioning
confidence: 99%
“…Kevetter and Leonard (1997) showed that the two populations of calbindin-labeled fibers were differentially distributed, with cerebellar and not vestibular afferents going to the parvocellular and central subdivisions of the VMN, regions which on geographic grounds would include the dense zones of calbindin fiber immunoreactivity seen in cat. Further evidence for the cerebellum as the source of the calbindin dense fiber patches comes from a study of a mouse mutant that lacks Purkinje cells (Bäurle et al 1998).…”
Section: Functional Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies on the calcium-binding protein levels in the auditory brainstem and central visual nervous system (Lane et al, 1996;Caicedo et al, 1997). However, there are only a few reports on the central vestibular system, and they mainly been focused on the role of calcium-binding proteins as a marker of afferent input, by using calretinin only or calretinin and calbindin after the recovery of static vestibular symptoms (Sans et al, 1995;Kevetter & Neonard, 1997). Sans et al (1995) reported that unilateral sensory deprivation induces permanent asymmetry in the expression of calretinin between the ipsilateral and contralateral MVN, and suggested that the calretinin expression in the MVN depends upon the integrity and activity of the sensorineural peripheral vestibular influences.…”
Section: mentioning
confidence: 99%
“…Sans et al (1995) reported that unilateral sensory deprivation induces permanent asymmetry in the expression of calretinin between the ipsilateral and contralateral MVN, and suggested that the calretinin expression in the MVN depends upon the integrity and activity of the sensorineural peripheral vestibular influences. Kevetter and Neonard (1997) reported that the level of calretinin and calbindin expression decreases after a vestibular neurectomy, and suggested that calretinin and calbindin are effective markers for identifying the vestibular afferents.…”
Section: mentioning
confidence: 99%